Nivel de estrés en estudiantes de pregrado II a X semestre de odontología durante la pandemia Covid 19 y su relación con el rendimiento académico. (2022)
Levels of perceived psychological stress in higher education students are seen to be associated with poor academic outcomes during the COVID-19 pandemic. Stress is a physiological response of the body to an external stimulus that disrupts its equilibrium, psychosocial factors often affect the mental health of students. Academic performance is affected by external factors such as emotional and psychological disturbances, family relationships, communication with teachers and the work status of university students. High levels of stress and anxiety in students have been determinant agents for academic stress.